Long-term evolution in liver fibrosis and immune profile after direct-acting antivirals therapy in hepatitis C virus-human immunodeficiency virus co-infected patients. (April 2022) - Laguno, Montserrat; Martínez-Rebollar, María; Casanova, Martina; de Lazzari, Elisa; González-Cordón, Ana; Torres, Berta; Inciarte, Alexy; Mora, Lorena de la; Ugarte, Ainoa; Ambrosioni, Juan; Blanco, José Luís; Martínez, Esteban; et al.
Abstract: Objective: Hepatitis C virus (HCV) therapy with direct-acting antivirals (DAA) achieves high rates of sustained virological response in people living with human immunodeficiency virus (HIV) (PLWH). Information on its long-term clinical impact is scarce. The aim of this study was to analyse liver fibrosis and immune response evolution after DAA treatment. Methods: Retrospective, single centre cohort study of HIV-HCV co-infected patients treated with DAA between June 2013 and June 2018. We analysed the changes during follow up in liver fibrosis (assessed by transient elastography (TE), aspartate aminotransferase to platelet ratio index (APRI) and FIB-4 scores) and immunity (CD4 and CD8 cells counts and CD4/CD8 ratio). Results: We included 410 patients; 75% (308/407) men with a mean age of 50 years (SD 8); 78% (318/410) had long chronic HCV infection (median 21 years, interquartile range (IQR) 6–27 years) and 27% (107/393) had liver cirrhosis. Liver fibrosis improvement based on the decrease in TE value compared with the baseline occurred in 43% (131/302) of patients and 31% of patients based on biological scores (APRI: 124/398; FIB-4: 104/398) (p < 0.0001), being more frequent in those with advanced baseline fibrosis (83/144). The higher decrease was observed at 6 months after DAA therapy (–0.23; 95% CI –0.29 to –0.18), but a continuum in fibrosis regression of at least 30% from baseline value of TE was observed along the follow up (32% of patients at month 6, 51% at month 24 and 55% at month 48). Regarding the immunological profile, there was a significant decrease in CD8 counts at month 48 (–62.38; 95% CI –106.77 to –17.99; p 0.0001) and a progressive rise in the CD4/CD8 ratio after 24 months of follow up reaching an increment of +0.07 (95% CI 0.03–0.10, p 0.0001) at month 48. Conclusions: HCV treatment with DAA in PLWH is associated with significant progressive improvement in liver fibrosis and recovery of the immune system with an increase in the CD4/CD8 ratio in long-term follow up.